Guns, gags and trolls: Disinformation and censorship are shaping the India–Pakistan conflict - GV South Asia (Global Voices, 2025)
India's “Operation Sindoor” sparked Pakistani retaliation and edged both nuclear-armed nations toward war, while Indian TV channels erupted in disinformation, blaring sirens, shouting anchors, and viral fake videos.
Pakistan